Mucosally delivered Salmonella Typhi expressing the Yersinia pestis F1 antigen elicits mucosal and systemic immunity early in life and primes the neonatal immune system for a vigorous anamnestic response to parenteral F1 boost - Ramirez, Karina (2009)
Neonates respond poorly to conventional vaccines. This has been attributed, in part, to the immaturity of neonatal dendritic cells (DC) that lack full capacity for Ag presentation and T cell stimulation. We engineered an attenuated Salmonella Typhi strain to express and export the F1 Ag of Y. pestis (S. Typhi(F1)) and investigated its immunogenicity early in life using a heterologous prime-boost regimen. Newborn mice primed intranasally with a single dose of S. Typhi(F1) elicited mucosal Ab- and IFN-γ secreting cells 1 wk after immunization. They also developed a potent and fast anamnestic response to a subsequent parenteral boost with F1-alum, which surpassed those of mice primed and boosted with S. Typhi(F1) or F1-alum. Neonatal priming with S. Typhi(F1), as opposed to priming with F1-alum, resulted in a more balanced IgG2a/IgG1 profile, enhanced avidity maturation and stimulation of B memory cells, and strong Th1-type cell-mediated immunity. S. Typhi(F1) enhanced the activation and maturation of neonatal CD11c(+) dendritic cells, shown by increased expression of CD80, CD86, CD40 and MHC-II cell surface markers and production of pro-inflammatory cytokines IL-12, TNF-α, IL-6 and MCP-1. S. Typhi(F1)-stimulated neonatal DC had improved capacity for Ag presentation and T cell stimulation in vitro and induced F1-specific CD4(+) and CD8(+) T cell responses when adoptively transferred to newborn mice. Mucosal immunization with S. Typhi expressing a foreign Ag effectively primes the neonatal immune system for potent, fast, and broader responses to a parenteral Ag boost. Such a strategy can prevent infectious diseases, including those considered biowarfare threats, early in life.